Sebaceous lymphadenoma of the parotid gland - Aparajita Mishra; Kalpalata Tripathi; Lity Mohanty; Manjulata Nayak (Wolters Kluwer Medknow Publications, 2011)
Sebaceous lymphadenoma is a rare benign salivary gland tumor of uncertain histogenesis. We report such a case in a 37-year-old female presenting with a parotid swelling. Recognition of key histological features will readily allow differentiation of this neoplasm from its benign and malignant mimics. The prognosis is excellent following excision.